Synopsis: Assessing the economywide impacts of COVID-19 on Rwanda’s economy, agri food system, and poverty: A social accounting matrix (SAM) multiplier approach - Aragie, Emerta A.; Diao, Xinshen; Robinson, Sherman; Rosenbach, Gracie; Spielman, David J.; Thurlow, James (International Food Policy Research Institute, 2021)
Rwanda’s response to COVID-19 has been widely praised for its rapid, systematic, and comprehensive approach to containing the pandemic. Although the economic consequences of the actions taken are unavoidable, the country expects to return its economy to its high-growth trajectory as the pandemic subsides. We used economic modeling tools designed to estimate the short-term economywide impacts of the unanticipated, rapid-onset economic shocks of COVID-19 on Rwanda. In this brief, we present a synopsis of the results of this analysis. • During the six-week lockdown that began in March 2020, we estimate Rwanda’s GDP fell 39.1 percent (RWF 435 billion; USD 484 million) when compared to a no-COVID situation. • Rwanda’s GDP in 2020 will be between 12 and 16 percent lower than a predicted no-COVID GDP, depending on the pace of economic recovery. The losses in annual GDP are between RWF 1.0 and 1.5 trillion (USD 1.1 to 1.6 billion). • While GDP for the industrial and services sectors were estimated to have fallen during the lockdown period by 57 and 48 percent, respectively, exemptions of COVID-19 restrictions for the agricultural sector limited the decline in agricultural GDP to 7 percent compared to a no-COVID situation. • During the lockdown period, the national poverty rate is estimated to have increased by 10.9 percentage points as 1.3 million people, mostly in rural areas, fell into temporary poverty. Poverty rates are expected to stabilize by the end of 2020, increasing only by between 0.4 and 1.1 percentage points over the pre-COVID situation. While these figures are encouraging, they mask the impacts on poor households of the sharp poverty spike during the lockdown and the inherent complexity of poverty dynamics post-lockdown. Looking forward, the speed and success of Rwanda’s economic recovery will depend critically on expanding Rwanda’s social protection programs, supporting enterprises of all sizes, providing broad assistance to the agri-food system, and restoring international trade.